ACCDB: A collection of chemistry databases for broad computational purposes. Issue 6 (23rd December 2018) - Morgante, Pierpaolo; Peverati, Roberto
Abstract : The importance of databases of reliable and accurate data in chemistry has substantially increased in the past two decades. Their main usage is to parametrize electronic structure theory methods, and to assess their capabilities and accuracy for a broad set of chemical problems. The collection we present here—ACCDB—includes data from 16 different research groups, for a total of 44, 931 unique reference data points, all at a level of theory significantly higher than density functional theory, and covering most of the periodic table. It is composed of five databases taken from literature (GMTKN, MGCDB84, Minnesota2015, DP284, and W4‐17), two newly developed reaction energy databases (W4‐17‐RE and MN‐RE), and a new collection of databases containing transition metals. A set of expandable software tools for its manipulation is also presented here for the first time, as well as a case study where ACCDB is used for benchmarking commercial CPUs for chemistry calculations. © 2018 Wiley Periodicals, Inc. Abstract : ACCDB—A Collection of Chemistry DataBases—includes five previously published databases from different sources (GMTKN, MGCDB84, DP284, Minnesota2015B, and W4‐17), and three new one (W4‐17‐RE, MN‐RE, and Metals&EE), and it includes 44, 931 unique reference data (all at a level significantly higher than DFT), and 10, 049 structures. Software tools for manipulation of ACCDB are also presented, as well as a case study for the performance of commercial CPUs for quantum chemistry calculations.